User's manual to accompany statistical analysis for engineers and scientists : - Barnes, J. Wesley (McGraw-Hill, 1994)
Simulation of a finite discrete space. Evaluating factorials, permutations, and combinations. Distributions evaluators. Plotting probability distribtion functions and other univariate functions.